The Effect of Digital Marketing, Brand Image and Perceived Value on Consumer Loyalty (Case Study on Citilink Airline Bali Branch) - I Komang Sumerta; I Gede Sukma Kiswara (Jurnal Scientia, 2022)
Post-purchase behavior is the focus of this study because it can show consumer loyalty to a product. Consumer loyalty is a commitment from consumers to a product that arises as a result of repeated purchases to provide benefits for producers or companies. This study aims to examine the effect of digital marketing, brand image, and perceived value on consumer loyalty. The sample used is as many as 110 respondents who have purchased flight ticket products for Citilink Bali Branch. The analysis technique used is multiple linear regression analysis. The results of the study found that simultaneously digital marketing, brand image, and perceived value affected consumer loyalty. Partially, digital marketing has a positive and insignificant effect on consumer loyalty. Brand image and perceived value have a positive and significant effect on consumer loyalty. Respondents gave the highest score on trust in Citilink's brand image and feeling happy while traveling using Citilink. Other attributes that get the lowest score must be the focus of improvement by Citilink to maintain customer loyalty in the long term.